A mobile learning application for Malaysian sign language - Azizul Hassan, Aini Faridah; Mohamad, Humaira; Zulkifle, Nur Izyani; Zainudin, Nur Sabrina; Robi, Putri Kharisma (2025)
The number of hearing-impaired people has gradually increased in Malaysia, which necessitates sign language skills. Since the establishment of the Malaysian Federation of the Deaf in 1998, Malaysian Sign Language (BIM) has been used as the primary means of communication for the deaf-mute community in Malaysia. Hearing individuals should be encouraged to learn and practice sign language in an effort to bridge the communication gap and improve accessibility. The significance of this study lies in the novel opportunity it provides for hearing learners to learn BIM through effective methods which have never before seen in the Malaysian context. This is in line with the growing need for accessible BIM references which are scarcely available in Malaysia to date which necessitates unique innovations of this kind. Hence, this study aims to design a mobile application that can facilitate the learning of BIM by using the Figma designing tool. With respect to the standards in BIM, the researchers self-produce the contents related to the hand gestures that represent the signs. The application is then tested by having beginner learners use it. The results indicate that the learners are able to benefit from it through the lessons and exercises provided which suit their proficiency level as beginners. It can be deduced that this application helps BIM learners to grasp the foundational concepts of sign language which allows them to understand diversity and break social barriers.